Basis of mathematics and methods of teaching - Kiseliovas, Arkadijus; Genienė, Danutė (Lietuvos matematikos rinkinys, 1998)
In the article is analyzed problems of alteration and integration of mathematical basis and its teaching methods that is lecturing at Pedagogical faculty.